Achieving Environmental Sustainability of Sugarcane Industry in Egypt: An Application of Life Cycle Assessment - Nakhla, Dalia Adel Habib (AUC Knowledge Fountain, 2015)
Sugarcane industry in Egypt goes back to the year 710 AD. Cane plantations are concentrated in the area of Upper Egypt. The total amount of cane cultivated in Upper Egypt is about 16 million tons per year. There are eight sugarcane producing factories in Egypt, most of them located close to the cultivations. The sugarcane industry in Egypt can be currently defined as an open industrial system that consumes material and energy and creates products and wastes. The two main stages of sugarcane production are the agricultural stage and the industrial stage. The agricultural stage involves cane cultivation which involves the use of fertilizers, water and fuel for irrigation, and cane harvesting which results in the production of two main residues which are cane tops and dry leaves. The cane tops are collected and used by the farmers to feed their livestock. The dry leaves, on the other hand, are openly burnt resulting in pollution of the ambient air. The cane is transported from the fields to the mills mainly by the sugarcane train. In the mill, the production process involves the consumption of chemicals, water and fuel to produce a number of by-products in addition to the main two products: raw sugar and molasses. The main residues or by-products are filter mud residing from the juice clarification process, bagasse from the cane squeezing and furnace ash in case the bagasse is burnt in the power house to provide steam and electricity for the mill. The filter mud and furnace ash are used in their raw form as soil additive due to their nutritional value. The bagasse, on the other hand, is either burnt in the mill power house to provide steam and electricity to the mill, or is directed to auxiliary factories to produce paper or fiberboard. The main aspects that have contributed to the research motivation: (1) mismanagement of the considerable amounts of residues generated during sugarcane harvest and its associated negative environmental impacts, (2) lack of tools and data for assessment of waste management alternatives based on environmental criteria rather than economic ones, (3) lack of low cost sustainable waste management options for sugar cane industry to achieve environmental balance. This research aims at assessing the environmental sustainability of the sugar industry in Egypt to achieve an environmentally balanced industry approaching zero waste. This is done by analyzing the current practices of reuse/recycling of by-products/residues generated from the sugarcane industry from its agricultural and industrial stages, as well as propose alternative environmental friendly practices for reuse of residues, such as composting and silage production. To achieve this, the research is divided into stages; identification of main current and potential uses of residues in Egypt, data collection, and data analysis using Life Cycle Analysis approach. Primary data and information was collected through field visits, interviews and questionnaires. The data collected from secondary sources included books, journals, conference papers, governmental reports, international organizations’ statistics and websites. Pilot scale experimental composting and silage making was performed on a combination of agricultural and industrial residues of the sugarcane industry including green tops, dry leaves, filter mud, bagasse and furnace ash. Results of the different treatments were analyzed and recommendations on the best combinations were given in terms of the physical, chemical and biological characteristics of the produced compost or organic fertilizer. Life cycle assessment (LCA) is used to evaluate the environmental performance of the sugarcane industry in Egypt including its agricultural and industrial stages. It is also used to identify the most environmental friendly options for the reuse of the residues generated from the sugarcane industry. Alternatives uses of bagasse, a cane milling residue, in the generation of steam and electricity, or production of paper, fiberboard or compost is investigated. It is also compared to processes that produce the same product but through other raw material. Recommendations and limitations of each option are presented and discussed.